2022
DOI: 10.1021/acsomega.2c00857
|View full text |Cite
|
Sign up to set email alerts
|

Low-Barrier Hydrogen Bond in Fujikurin A–D: A Computational Study

Abstract: The compounds Fujikurin A, B, and D, recently isolated from Fusarium fujikuroi , possess intramolecular low-barrier hydrogen bonds (LBHBs), which are hydrogen bonds with a very low-energy barrier for proton transfer. The isolated compounds have a hydrogen-bonded proton that appears to rapidly switch between two equilibrium states via a transition state (TS). To understand the characteristics of these intramolecular LBHBs in detail, we performed path integral molecular dynamics (PIMD) sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For example, several groups and we have reported that NQEs of hydrogen nuclei enhance the hydrogen bond strength and facilitate proton transfer reactions. 19–24 Furthermore, we have also demonstrated that considering the NQEs is indispensable for the analysis of the H/D isotope effects. 24…”
Section: Introductionmentioning
confidence: 90%
“…For example, several groups and we have reported that NQEs of hydrogen nuclei enhance the hydrogen bond strength and facilitate proton transfer reactions. 19–24 Furthermore, we have also demonstrated that considering the NQEs is indispensable for the analysis of the H/D isotope effects. 24…”
Section: Introductionmentioning
confidence: 90%
“…We have already demonstrated that the NQE should be considered for the quantitative analysis of LBHB systems. 11–14 For such systems, CLMD results without NQE occasionally differ completely from PIMD results. In particular, the proton distributions obtained through CLMD and PIMD simulations should be quite different.…”
Section: Introductionmentioning
confidence: 96%
“…Since the PIMD simulations use MD simulation to calculate the statistical average, the PIMD simulations can take not only the NQEs but also thermal effects into account. Many research groups have investigated hydrogen-bonded systems with the aid of PIMD method, 22−30 to analyze the stationary point structures of the LBHB systems [22][23][24]29 at the finite temperature. Therefore, we decided to conduct a PIMD simulation on the PBD compound of hydrogen sulfate and formate in this study.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since the PIMD simulations use MD simulation to calculate the statistical average, the PIMD simulations can take not only the NQEs but also thermal effects into account. Many research groups have investigated hydrogen-bonded systems with the aid of PIMD method, and these studies demonstrated that the PIMD simulation is the suitable choice to analyze the stationary point structures of the LBHB systems , at the finite temperature.…”
Section: Introductionmentioning
confidence: 99%